Doença hepática gordurosa não alcoólica: avaliação histopatológica em biopsias por agulha e concordânciainterobservador - Cynthia Koeppel Berenstein (2007)
Nonalcoholic fatty liver disease (NAFLD) comprises a spectrum of lesions ranging from steatosis, steatohepatitis and cirrhosis to hepatocellular carcinoma, with nonalcoholic steatohepatitis (NASH) being the progressive form of NAFLD. NAFLD is suspected in the case of hepatomegaly upon clinical examination, fat accumulation in the liver on abdominal ultrasound and/or discrete (2 to 3 times the reference value) and persistently elevated (two or more occasions) aminotransferase levels in individuals presenting no other cause of these alterations (exclusion of other liver diseases). However, these work-up methodsonly suggest the diagnosis. Liver biopsy is the gold standard for the diagnosis of the disease and is the only method able to differentiate NASH from simple steatosis, to grade inflammation and to stage fibrosis. In the present study, we analyzed the histopathological findings of liver biopsies and interobserver agreement in the histological evaluation of cases with an histological diagnosis of steatosis or steatohepatitis, with or without fibrosis and with no history of alcohol abuse in the exam request, with emphasis on the establishment of minimal criteriafor the diagnosis of NASH. Seventy needle biopsies were analyzed according to Brunt et al (1999), with modifications. Discrete NASH (grade 1) was the most common form. If fibrosis was detected, stage 1 was the most frequent. Lobular inflammation determinated NASH´s grade. When fibrosis was present, increasing collagen deposition at zone 3, with septal formation, determinated stages 2 and 3. Interobserver agreement was very good for macrovesicular steatosis (KW = 0.82) and good for lobular inflammation (KW = 0,.68) and fibrosis (KW = 0.73). Theclassification of Brunt et al (1999), with the modifications introduced here, can be applied to the diagnosis not only of NASH but also of NAFLD, representing a reliable method for use in the daily practice of pathologists, besides diagnosing mild forms of NASH.